Effects of elective cesarean sections on perinatal outcomes and care practices - Anna Paula Ferrari; Maiara Aparecida Mialich Almeida; Maria Antonieta Barros Leite Carvalhaes; Cristina Maria Garcia de Lima Parada (Instituto Materno Infantil de Pernambuco, 2020)
Abstract Objectives: to verify the effects of elective cesarean sections on perinatal outcomes and care practices, as compared to vaginal deliveries. Methods: cohort study with 591 mothers and their babies, developed in a medium-sized city in the state of São Paulo, Brazil. Data were collected from hospital records and by interviews at the neonatal screening unit in the city from July 2015 to February 2016. Data regarding childbirth, newborns, sociodemography, and current gestational history were obtained from each mother. The associations of interest were evaluated with Cox regression analyses adjusted for the covariates identified through the results of bivariate analyses presenting a statistical significance level ofp<0.20. In adjusted analyzes, relationships were considered significant ifp<0.05, with relative risk being considered as the measure of effect. Results: if compared to women who had vaginal deliveries, those who were submitted to elective cesarean sections were at a higher risk of not having skin-to-skin contact with their babies in the delivery room, of not breastfeeding in the first hour of life, and of having their babies hospitalized in a neonatal unit. Conclusions: reducing the number of elective cesarean sections is essential to foster good neonatal care practices and reduce negative neonatal outcomes.